2020
DOI: 10.32479/ijeep.10218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Economic Growth and Foreign Direct Investment on Carbon Emission in the Asian States

Abstract: This research article analyzes the relationship between carbon dioxide gas emission, economic development, energy consumption and FDI in Asian states. The Autoregressive Distribution of Lag bounds tests has been applied for co-integration from 1970 to 2014. According to the results, there is a direct relationship between energy consumption and carbon dioxide gas emission. Moreover, there is no existence of a significant relationship between FDI and gas emission of carbon dioxide. In the long run, the coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…The coefficient indicates that a one-percent increase in economic growth will deteriorate environmental quality by about 1.26 percent in Model 1, that is 0.61 percent and 0.07 points in Model 2 and Model 3, respectively, which are all significant at 1% significance level. The negative effect is in line with findings by Bokpin (2017) whereas the positive impact on carbon emissions conforms with studies by Gunarto (2020), Aluko and Obalade (2020), Khan et al (2020), Ganda (2020) and Hao et al (2020).…”
Section: [Insert Table 9 Here]supporting
confidence: 91%
“…The coefficient indicates that a one-percent increase in economic growth will deteriorate environmental quality by about 1.26 percent in Model 1, that is 0.61 percent and 0.07 points in Model 2 and Model 3, respectively, which are all significant at 1% significance level. The negative effect is in line with findings by Bokpin (2017) whereas the positive impact on carbon emissions conforms with studies by Gunarto (2020), Aluko and Obalade (2020), Khan et al (2020), Ganda (2020) and Hao et al (2020).…”
Section: [Insert Table 9 Here]supporting
confidence: 91%
“…Ekwueme et al (2021) measures the variable by the ratio of industrial pollution control investment to GDP. Synthesizing the pros and cons of various indicators and the availability of data, this paper draws on the method of Gunarto (2020) to construct an environmental management system evaluation index. The advantage of this method is that the environmental management system indicators remove the structural factors of the industrial industry.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The study found that the foreign direct investment FDI inflows led to environmental degradation in the case of Brazil but it was not the case for Singapore. (Gunarto, 2020) analyzed the relationship between carbon dioxide gas emission, economic development, energy consumption, and FDI in Asian states for the period (1970 -2014). The results showed that there is a direct relationship between energy consumption and carbon dioxide gas emission, while there is no existence of a significant relationship between FDI and gas emission of carbon dioxide.…”
Section: Literature Reviewmentioning
confidence: 99%